Thyrotropin Receptor Antibody as a Risk Factor for the Occurrence and Severity of Graves' Ophthalmopathy - Ikhsan, Mohammad Robikhul; Kertia, Nyoman; Supanji, Supanji; Rianto, Bambang Udji Djoko (Acta Interna The Journal of Internal Medicine, 2023)
Background. Graves' disease (GD) is an autoimmune disorder known to be the most common cause of hyperthyroidism. Thyrotropin receptor antibody (TRAb) might be involved in the occurrence and the disease process of Graves’ ophthalmopathy (GO).Objectives. This study aimed to evaluate whether TRAb levels are associated with the occurrence and severity of GO based on the clinical severity of The European Group on Graves' Orbitopathy (EUGOGO).Methods. A case-control study of 44 patients with newly diagnosed Graves’ disease (22 with GO compared to 22 without GO). Diagnosis of GO was made according to Bartley and Gorman’s criteria. Level of thyrotropin receptor antibody was tested with electrochemiluminescence immunoassay (ECLIA) method. Assessment of the clinical severity of GO was documented with EUGOGO scores.Results. Baseline characteristics were similar between 22 patients with GO compared to 22 patients non-GO group. Thyrotropin receptor antibody (TRAb) significantly increased in the GO group (11.223±7.116 IU/L) when compared to non-GO (6.720±3.442 IU/L; P=0.035). Multiple logistic regression analysis shows that 1 IU/L increase of TRAb has a 1.610-fold higher risk for developing GO. In the GO group, there is correlation between TRAb and the severity of GO-based on EUGOGO (r =0.794, P<0.001).Conclusion. Thyrotropin receptors antibody is a risk factor for the occurrence and severity of GO-based on EUGOGO.